Effect of including oilseed grains in bovine diets on fatty acid profile, lipid stability, and sensory aspects of burgers - Brito, Thais Rayane Rios; Valeriano, Heitor Henrique Costa; Ítavo, Luís Carlos Vinhas; Duarte, Marjorie Toledo; Pereira, Marília Williani Filgueira; Corrêa, Samara Miyaki; Miyagusku, Luciana; Araújo, Thiago Luís Alves Campos de; Ítavo, Camila Celeste Brandão Ferreira; Gomes, Rodrigo da Costa; Gomes, Marina de Nadai Bonin (Frontiers in Veterinary Science, 2022)
The aim of this study was to evaluate the effect of including different oilseed grains in the diets of cattle on the qualitative and sensory characteristics and fatty acid profile of burger over a storage period of up to 120 days. The soybean diet increased 30% of ether extract in burgers when compared to the control diet. The inclusion of oilseeds in the bovine diet did not change the n-6/n-3 and hypocholesterolemic/hypercholesterolemic ratio, as well as the cholesterol levels in the burgers. The smallest flavor and aroma note scores were attributed to burgers produced with meat of bovine fed with cottonseed (4.35 and 4.67, respectively). The sunflower diet resulted in smaller lipid oxidation (1.03 mg/kg). The storage period increased lipid oxidation (0.43 and 1.97 mg/kg of malonaldehyde at 0 and 120 days, respectively). The inclusion of oilseeds in the diet of cattle does not change the ratios of fatty acids in burgers, which are important to human health. It is recommended to use soybean and sunflower grains in cattle diets to improve the sensory quality of burgers. A 30-day storage period is recommended to maintain the flavor and juiciness of beef burgers.